From Summer Cottage Colony to Metropolitan Suburb: Toronto's Beach District, 1889-1929 - Luka, Nik (Urban History Review / Revue d'histoire urbaine, 2006)
Over four decades beginning in the 1890s, the east-end Toronto district now known as “The Beach” was transformed from a summer second-home setting into a metropolitan suburb dominated by the middle classes (occupationally defined). Using a systematic random sample drawn from the municipal property tax assessment rolls for the study area at six intervals from 1889 to 1929, along with narrative examples and illustrative analyses of growth and change in urban form, this paper examines three compelling aspects of this transformation. First and foremost, this district is a fine example of pre-Second World War suburban growth: slow, piecemeal, and inconsistent in pattern and form, as now reflected in its eclectic built form and fine-grained mix of housing types. “The Beach” is also a place-based example of how metropolitan social geographies were being sorted out from within by user groups early in the twentieth century. Without becoming exclusively or solely a middle-class district, the Beach came to be dominated by the middle classes—typifying the “weave of small patterns” that characterized the social fabric of the early North American metropolis. Finally, the term cottage colony is used quite deliberately, for it appears that the Beach's role as a summer leisure destination was instrumental in spurring its transformation into a middle-class suburb, imbuing it with particular qualities that enhanced (or ensured) its desirability. In effect, this district's “summer cottage” period was a telling prelude to its emergence as a markedly middle-class district in Toronto of the 1920s and later.